TT-seq maps the human transient transcriptome - Schwalb, Bjorn; Michel, Margaux; Zacher, Benedikt; Fruehauf, Katja; Demel, Carina; Tresch, Achim; Gagneur, Julien; Cramer, Patrick (Science, 2016)
Pervasive transcription of the genome produces both stable and transient RNAs.We developed transient transcriptome sequencing (TT-seq), a protocol that uniformly maps the entire range of RNA-producing units and estimates rates of RNA synthesis and degradation. Application of TT-seq to human K562 cells recovers stable messenger RNAs and long intergenic noncoding RNAs and additionally maps transient enhancer, antisense, and promoter-associated RNAs. TT-seq analysis shows that enhancer RNAs are short-lived and lack U1 motifs and secondary structure.TT-seq also maps transient RNA downstream of polyadenylation sites and uncovers sites of transcription termination; we found, on average, four transcription termination sites, distributed in a windowwith amedianwidth of 3300 base pairs.Termination sites coincidewith a DNA motif associated with pausing of RNA polymerase before its release from the genome.
CRIS-Team Scopus Importer:2023-03-11